The Influence of Social Media Marketing of A Beauty Service SME on the Customer Purchase Decision - Riska, Riska; Koeswandi, Tika Annisa Lestari; Yusuf, Ismail (A Social Science and Entrepreneurship Journal, 2024)
This study aims to determine the description of Instagram social media marketing and purchasing decisions at MUA Amei Makeup, and to determine the effect of Instagram social media marketing on purchasing decisions at MUA Amei Makeup. This research uses quantitative research methods with descriptive and verification approaches. The data sources used are primary data and secondary data. In collecting data, researchers used observation, interviews and questionnaires. The sampling technique is probability sampling, where each member has the same opportunity to be selected as a sample. The population of this study were MUA Amei Makeup Instagram followers with a total of 1963 people, so a sample of 95 people was obtained. Data was collected using a questionnaire. The data analysis techniques used are descriptive statistics, classical assumption test, simple regression test, t test, and coefficient of determination. The results showed that Instagram social media marketing had a positive effect on purchasing decisions at MUA Amei Makeup by 31.3% while the remaining 68.7% was influenced by other variables such as marketing mix, socio-cultural influences, and communication consisting of advertising, buzz agents and word-of-mouth which were not examined in this study